New data on geometroid moths (Lepidoptera: Geometroidea: Uraniidae and Geometridae) from Sakhalin and Moneron islands with notes on their taxonomy, distribution and ecology - Beljaev, Evgeniy A.; Titova, Olga L. (Zootaxa, 2023)
The paper treats 51 species of geometroid moths (Lepidoptera: Uraniidae and Geometridae) from Sakhalin and Moneron islands, Russian Far East. Among them, one species (Trichopteryx fastuosa Inoue) is first reported from Russia; ten species—first recorded for Sakhalin (Uranidae Epipleminae: Eversmannia exornata (Eversmann), Dysaethria illotata (Christoph), and D. moza (Butler); Geometridae: Idiotephria evanescens (Staudinger), Lampropteryx minna (Butler), Lomographa simplicior (Butler), Pachyerannis obliquaria (Motschulsky), Venusia phasma (Butler), V. semistrigata (Christoph), and Zanclidia testacea (Butler), and two geometrid species—first recorded for Moneron (Acasis exviretata Inoue, and Abraxas niphonibia Wehrli). For 26 species, which Beljaev and Mironov (2019) first noted for Sakhalin without label data on the specimens, relevant materials are published. For nine species previously recorded from Sakhalin by single or few specimens or whose habitation on the island was in doubt, new confirming data are provided. For eight species erroneously reported from Sakhalin, their identifications are corrected and they are excluded from the fauna of the island (“Acasis appensata”, “Comibaena tancrei”, “Dysstroma korbi”, “Eilicrinia nuptaria”, “Eupithecia neosatyrata”, “Myrioblephara nanaria”, “Photoscotosia lucicolens”, and “Trichopteryx incerta”). The nominal taxon Eupithecia consueta Butler is restored from a synonymy with Pasiphila chloerata (Mabille) as a subspecies Pasiphila chloerata consueta (Butler), stat. n. In Trichopteryx Hübner and Pasiphila Meyrick, the presence of two “cryptic” species in East Asia is suggested. Extended notes on the general distribution, misidentifications and / or identification characters are provided for Eversmannia exornata, Dysaethria illotata, D. moza, Abraxas niphonibia, Acasis exviretata, Dysstroma citrata (Linnaeus), Eulithis achatinellaria (Oberthür), Ecliptopera pryeri (Butler), Idaea foedata (Butler), Laciniodes denigrata Warren, Lampropteryx minna (Butler), Larerannis orthogrammaria (Wehrli), Lomographa simplicior, Pasiphila chloerata (Mabille), Perizoma alchemillata (Linnaeus), Photoscotosia atrostrigata (Bremer), Platycerota incertaria (Leech), Timandra rectistrigaria (Eversmann), Trichopteryx hemana (Butler), Venusia phasma, V. semistrigata, and Xanthorhoe hortensiaria (Graeser). The keys to Trichopteryx carpinata (Borkhausen) and T. ignorata Inoue; to Eulithis achatinellaria and E. testata (Linnaeus); to Ecliptopera pryeri, E. silaceata leuca (Djakonov), and E. capitata capitulata (Staudinger), are given. In addition to data on Sakhalin, Dysaethria illotata is reported for the first time from the Kuril Islands, Dysaethria cretacea (Butler) is excluded from the fauna of Russia, Acasis exviretata is excluded from the continental Asian fauna, Xanthorhoe evae Viidalepp & Remm, is reported for the first time from China, and Lampropteryx minna and L. denigrata are excluded from the fauna of Mongolia. A series of reidentifications of the specimens from the BOLD and GBIF databases is suggested. Observations in nature, local and general distribution, biogeography and ecology of the considered Sakhalin geometrid moths, as well as their possible invasions of the island, are also briefly discussed.